2017
DOI: 10.1093/bja/aex300
|View full text |Cite
|
Sign up to set email alerts
|

Surgical pleth index: prediction of postoperative pain in children?

Abstract: ACTRN12616001139460.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 10 publications
1
25
0
1
Order By: Relevance
“…In fact, a recent own investigation of the predictive value of SPI in different aged children concluded that SPI performed differently across the age groups. 14 Though all aforementioned results show significant limitations in the value of SPI for the prediction of postoperative pain, it is worth keeping in mind that we also confirmed the even lower value of MAP and HR for this task, with these parameters being as predictive for postoperative pain as tossing a coin. Similar results have been reported previously.…”
Section: Discussionsupporting
confidence: 67%
“…In fact, a recent own investigation of the predictive value of SPI in different aged children concluded that SPI performed differently across the age groups. 14 Though all aforementioned results show significant limitations in the value of SPI for the prediction of postoperative pain, it is worth keeping in mind that we also confirmed the even lower value of MAP and HR for this task, with these parameters being as predictive for postoperative pain as tossing a coin. Similar results have been reported previously.…”
Section: Discussionsupporting
confidence: 67%
“…SPI values, which indicate surgical stress reactions, range between 0 and 100, with 0 representing the lowest stimulus response and 100 representing the highest level of stimulation. High SPI values are considered indicators of a prevalence of nociception over antinociception [7]. Surgical procedures under general anesthesia elicit a variety of stress responses that induce negative influences and that eventually negatively affect patients' prognosis [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SPI can estimate intraoperative nociception. SPI ranges from 0 to 100, and higher values indicate stronger stimuli during surgery [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence for this recommendation is relatively sparse. Two studies have postulated that the 'ideal' SPI may be significantly influenced by age (children vs adults), 62 and that it could be possibly lower (i.e. at or below 30).…”
Section: Two-parameter Scoresmentioning
confidence: 99%